Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11064-009-9917-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant Activity of Valeriana officinalis Against Different Neurotoxic Agents

Abstract: Valeriana officinalis L. (Valerian) is widely used as a traditional medicine to improve the quality of sleep. Although V. officinalis have been well documented as promising pharmacological agent; the exact mechanisms by which this plant act is still unknown. Limited literature data have indicated that V. officinalis extracts can exhibit antioxidant properties against iron in hippocampal neurons in vitro. However, there is no data available about the possible antioxidant effect of V. officinalis against other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 39 publications
(49 reference statements)
2
29
0
1
Order By: Relevance
“…Yoo et al (2015) showed that the inhibitory effect of the valerian extract on microglia may protect hippocampal neurons from ischemic damage. The results from these authors support the previous observation that the valerian extract ameliorates the reduction of total thiol content in homogenates and also decreases H 2 O 2 production in the mitochondria of flies exposed to rotenone (Sudati et al, 2009). Thus, the administration of valerian extract significantly increases neuronal survival after ischemia/reperfusion by decreasing reactive microglia and the levels of lipid peroxidation (Yoo et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
“…Yoo et al (2015) showed that the inhibitory effect of the valerian extract on microglia may protect hippocampal neurons from ischemic damage. The results from these authors support the previous observation that the valerian extract ameliorates the reduction of total thiol content in homogenates and also decreases H 2 O 2 production in the mitochondria of flies exposed to rotenone (Sudati et al, 2009). Thus, the administration of valerian extract significantly increases neuronal survival after ischemia/reperfusion by decreasing reactive microglia and the levels of lipid peroxidation (Yoo et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
“…This was assayed by a standard method [17]. Deoxyribose is degraded by hydroxyl radicals with the release of thiobarbituric acid (TBA) reactive materials.…”
Section: Hydroxyl Radical Scavengingmentioning
confidence: 99%
“…2 million adults) had used valerian in the past week [5]. Other studies indicate that VE has antioxidant and neuroprotective effects [6,7,8,9]. Furthermore, VE modulates brain neurotransmitters [10,11,12,13,14], and shows antianxiety, antidepressant, and antiepileptic activity in animal models [15,16].…”
Section: Introductionmentioning
confidence: 99%